Shared Demands Between Cognitive and Physical Tasks May Drive Negative Effects of Fatigue: A Focused Review - Aitken, Blair; MacMahon, Clare (Frontiers in Sports and Active Living, 2019)
Over the last decade, there has been increasing interest in the effects of cognitive fatigue on physical performance. This review aims to provide an understanding of these effects with an emphasis on different types of physical tasks requiring different cognitive loads. Taken together, the research shows that endurance performance and cognitive-perceptual skills seem to decline following the completion of a cognitive task, while anaerobic performance remains unaffected. Consistent with the limited-resource model of self-control, the completion of a cognitively demanding task may deplete or inhibit cognitive resources, resulting in impaired performance on a subsequent physical task that relies on similar resources. In other words, physical tasks involving central executive functioning may be significantly more impaired by cognitive fatigue compared to tasks that utilise an all-out strategy. It is recommended that future research continues examining the impact of cognitive fatigue on different types of physical tasks while controlling for other variables.